2019
DOI: 10.3390/coatings9090543
|View full text |Cite
|
Sign up to set email alerts
|

Influence of LBE Temperatures on the Microstructure and Properties of Crystalline and Amorphous Multiphase Ceramic Coatings

Abstract: An Al2O3–TiO2 amorphous composite coating with a thickness of 100–120 μm was fabricated on China low activation martensitic steel (CLAM steel) by oxygen acetylene flame spraying technology and the laser in-situ reaction method. We investigated the microstructures and mechanical properties of the coating after liquid lead-bismuth eutectic (LBE) alloy corrosion under different temperatures for 300 h and found that the corrosion temperature of the LBE had no observable effect on the microstructure and chemical ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Higher swelling resistance is pursued via microstructure stabilisation with selected alloying elements (for instance AIM1 and its bettered version AIM2) [269][270][271]. Enhanced corrosion resistance is sought for with corrosion barriers, either by implanting aluminum to change the surface composition and induce the formation of a protective alumina layer [272,273], or by directly depositing alumina (or other ceramics) layers to coat the metallic substrate [274][275][276]. Alternatively, aluminum is added to the alloy composition, to enable the formation of a protective alumina layer that self-heals through contact with the oxygen that is contained in the circulating fluids, so-called alumina forming austenitic (AFA) steels [277][278][279][280][281].…”
Section: Annex 3-pathways To Nuclear Materials Improvement For Next G...mentioning
confidence: 99%
“…Higher swelling resistance is pursued via microstructure stabilisation with selected alloying elements (for instance AIM1 and its bettered version AIM2) [269][270][271]. Enhanced corrosion resistance is sought for with corrosion barriers, either by implanting aluminum to change the surface composition and induce the formation of a protective alumina layer [272,273], or by directly depositing alumina (or other ceramics) layers to coat the metallic substrate [274][275][276]. Alternatively, aluminum is added to the alloy composition, to enable the formation of a protective alumina layer that self-heals through contact with the oxygen that is contained in the circulating fluids, so-called alumina forming austenitic (AFA) steels [277][278][279][280][281].…”
Section: Annex 3-pathways To Nuclear Materials Improvement For Next G...mentioning
confidence: 99%
“…However, the coating often exhibits low density and high porosity and contains numerous defects such as cracks or oxide inclusions. To overcome this disadvantage, Chen et al [54,55] combined successively the thermal spraying and the laser surface re-melting in-situ reaction technique in order to attempt having high quality coating Al 2 O 3 -TiO 2 on the Chinese low activation martensitic (CLAM) steel, a steel that contains 8.91% Cr, 1.44% W, 0.35% Mn, 0.15% Ta, and 0.13% C. First, a FeCrAlTi composite powder was obtained by ball milling, heating, stirring, and drying and broken treatment of a Cr-Fe, Fe-Al, and Ti powder. The oxyacetylene flame-spraying technology was applied first to fabricate the CrFeAlTi coating, and the laser in situ reaction compound technology was then adopted to prepare the composite ceramic coating using the CO 2 laser system.…”
Section: Al 2 O 3 -Tio 2 Coating By Thermal Spraying Technology and Laser In-situ Reaction Methodsmentioning
confidence: 99%
“…A first trial in liquid lead for a duration up to 1000 h showed that the coating prevented Pb from diffusing and therefore featured potential applications in heavy liquid metals [54]. After exposure of the coated CLAM in LBE [55] without control of oxygen for 300 h at 450 and 550 • C, neither the Pb signal nor Bi signal were detected in the very surface of the CLAM steel. In addition, the Al 2 O 3 -TiO 2 coating exhibited a hydrophobic property on LBE, which is in favorable for LME resistance.…”
Section: Al 2 O 3 -Tio 2 Coating By Thermal Spraying Technology and Laser In-situ Reaction Methodsmentioning
confidence: 99%
“…Candidate coating materials that aim primarily at limiting and/or preventing undesirable LMC effects include refractory metals [180,243,626], Al-or Si-containing metallic alloys [192,525,596,[626][627][628][629][630][631][632], and certain ceramic materials [243,626,[632][633][634][635].…”
Section: Coating Deposition and Surface Modification Of Steelsmentioning
confidence: 99%